Integrating Local Wisdom and Scientific Inquiry in Early Childhood Education: A Contextualized Science Learning Approach - Suharti Suharti; Hapidin Hapidin; Yuli Pujianti; Edi Suwandi; Muhammad Naufal Fairuzillah (Atfaluna: Journal of Islamic Early Childhood Education, 2025)
This study explores the integration of local wisdom and scientific inquiry in early childhood education (ECE) on Untung Jawa Island, Administrative City of Kepulauan Seribu, DKI Jakarta. Employing a mixed-method approach, the quantitative phase utilized a one-shot posttest experimental design involving 21 children aged 5-6 years old, consisting of 11 boys and 10 girls. The children participated in culturally contextualized science activities that incorporated local wisdom. In addition to quantitative data collection, qualitative data were gathered through observations and interviews with five ECE teachers to gain deeper insights into the implementation process. The results indicate that integrating local wisdom enhances children's engagement and understanding of scientific concepts. This study recommends further research to explore long-term impacts and broader applications of culturally responsive teaching methods in early childhood settings.